From Fushā to Arabizi: The Transformation of Journalistic Language and the Social Life of Arab Society in the Era of Electronic Media - Dian Melinda (Journal of Digital Arabic Language Education, 2026)
Electronic media have fundamentally transformed the way societies including Arab societies access information, form opinions, and interact with one another. This article analyzes three issues: (1) the transformation of journalistic language accompanying the shift from print to electronic and digital media, with particular emphasis on the dynamics of digital Arabic in social media and online journalism; (2) the role of electronic media, particularly television and social media platforms, in the social life of contemporary Arab society; and (3) the theoretical frameworks relevant to understanding these phenomena. This study employs a descriptive-analytical qualitative method grounded in systematic library research of 21 primary and secondary sources published between 1978 and 2026, analyzed through the lens of Uses and Gratifications Theory and Agenda-Setting Theory. The findings indicate that electronic journalistic language is characterized by conciseness, speed, and interactivity, while in the Arab context specifically, phenomena such as Arabizi (Arabic-Latin transliteration), Arabic-English code-switching, and a shift in dominance from Modern Standard Arabic (Fusha) to colloquial dialects (Ammiyah) have emerged in informal digital communication. Electronic media were further found to exert a dual influence on Arab society: expanding access to information and facilitating social movements including their documented role in Arab Spring coverage while also contributing to the spread of misinformation, digital privacy concerns, and a potential erosion of formal Arabic language competence among younger generations. This article recommends strengthening both media literacy and digital language literacy in the Arab world as a mitigating measure.